ANALISIS FRAMING PEMBERITAAN BASUKI TJAHAJA PURNAMA (AHOK) TERKAIT ISU SARA DALAM PILKADA DKI JAKARTA TAHUN 2017 DALAM MEDIA ONLINE KOMPAS.COM - Roy Marten; Dina Fadiyah (Universitas 17 Agustus 1945 Jakarta, 2020)
The Purpose of this paper research is to find out how the framing conducted by Kompas.com Media Associated with alleged blasphemy by Basuki Tjahaja Purnama, and want to see more about the procedures or techniques used by Kompas.com in placing and positioning related news the issues of sara or blasphemy by Ahok. As for analyzing this, the writer used the framing model of Pan and Gerald M. Kosicki, in which there are 4 types of structure, namely, syntactic structure (the way journalists compile facts), script structures (how journalists tell facts), thematic structures (how journalist write facts) and rhetorical structure (the way journalist emphasize facts). As well as looking at the relationship between the media and politics in the Ahok case with media and political theory.In writing this paper the writer used qualitative methods. The results of this research Media Kompas.com appear neutral in reporting the news by presenting many sources, imformants and imformation in supporting the news reported. However, on the other hand, Kompas.com indirectly made certain protests in certain directions with a point of view that aligned with the suspect Basuki Tjahaja Purnama on the news displayed by Kompas.com